Beyond the business cycle: Factors driving aggregate mortality rates - Katja Hanewald (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
This article provides a comprehensive econometric analysis of factors driving aggregate mortality rates over time. It differs from previous studies in this field by simultaneously considering an extensive set of macroeconomic, socio-economic and ecological factors as explanatory variables. Germany is chosen as an indicative example for other industrialized countries due to its advanced demographic transition process. Our regression analysis, which covers the time interval 1956-2004, indicates that sex- and age-specific mortality rates vary substantially in their response to external factors. Strongest associations are found with changes in real GDP, flu epidemics and the two life style variables alcohol and cigarette consumption in both univariate and multivariate setups. Further analysis shows that these effects are primarily contemporary, while other indicators such as weather conditions exert lagged effects. By combining variables in a multivariate model the share of explained data volatility can be substantially increased.
Keywords: I12; J11; C32; 330; Aggregate mortality; business cycle; socio-economic factors; multivariate model; Sterblichkeit; Konjunktur; Lifestyle; Multivariate Analyse; Schätzung; Deutschland